The founder : Cecil Rhodes and the pursuit of power - Rotberg, Robert I. (Oxford University Press, 1988)
A tall, robust-looking, imposing figure, Cecil John Rhodes was a man of many contradictions. Rhodes, the dreamy idealist, called his copy of The Meditations of Marcus Aurelius his "most precious possession," while Rhodes, the ruthless businessman, firmly believed in the adage, "every man has his price." He supported invidious racial laws in South Africa, and invented and sponsored the world-renowned Rhodes Scholarships. Although a man of unprepossessing intellectual talents, he became one of the leading figures in the English-speaking world, the confidant of Queen Victoria